Performance of National Unity and Political Agency Office Employees in Gayo Lues Regency - Asmaini*, Asmaini; Kelana, Edy Putra; Aisyah, Siti (Universitas Syiah Kuala, 2024)
The problem that occurs is the performance of the Kesbangpol Office employees who are not disciplined during working hours, the community assesses that the quality of the performance provided is still not optimal, the community waits for the arrival of employees, resulting in time delays in providing services to the community. In providing services, it also does not meet the standards as expected. This research aims to analyze the performance and determine the obstacles to employee performance at the Gayo Lues Regency Kesbangpol Agency in Public Services. This type of research uses a qualitative descriptive approach. The theory used is Dwiyanto's theory of performance including productivity, service quality, responsiveness and accountability. The results of this research are the performance of the Gayo Lues Regency National Unity and Political Staff, namely that productivity has not been fully achieved according to the target, quality of service on a priority scale in determining the most important needs to be met first, responsibility for implementing Standard Operational Standards (SOP) is able to improve service quality, Accountability. Implementation of activities is in accordance with the schedule so that programs and activities run properly. Obstacles found in the performance of ASN at Kesbangpol include, among other things, the absence of Standard Operating Procedures (SOP) so that there is no reference in providing services to the community, especially regarding who is implementing it, service time and limited human resources as program implementers, as well as obstacles in terms of limited availability. Facilities and infrastructure.